Exploration of joint working practices on anti‐social behaviour between criminal justice, mental health and social care agencies: A qualitative study. (18th January 2018) - Krayer, Anne; Robinson, Catherine A.; Poole, Rob
Abstract: Although the police play an important role for people with mental health problems in the community, little is known about joint working practices between mental health, social care and police services. There is potential for tensions and negative outcomes for people with mental health problems, in particular when the focus is on behaviours that could be interpreted as anti‐social. This study explores perceptions about joint working between mental health, social care and police services with regard to anti‐social behaviour. We conducted a multi‐method sequential qualitative study in the UK collecting data between April 2014 and August 2016. Data were collected from two study sites: 60 narrative police logs of routinely gathered information, and semi‐structured interviews and focus groups with professionals from a range of statutory and third sector organisations ( N  = 55). Data sets were analysed individually, using thematic iterative coding before integrating the findings. We also looked at sequencing and turning points in the police logs. Findings mapped on a continuum of joint working practices, with examples more likely to be away from the policy ideal of partnership working as being central to mainstream activities. Joint working was driven by legal obligations and concerns about risk rather than a focus on the needs of a person with mental health problems. This was complicated by different perceptions of the police role in mental health. Adding anti‐social behaviour to this mix intensified challenges as conceptualisation of the nature of the problem and agreeing on best practice and care is open to interpretations and judgements. Of concern is an evident lack of awareness of these issues. There is a need to reflect on joint working practices, including processes and goals, keeping in mind the health and welfare needs of people with mental health problems.